S-Nitrosation of Cellular Proteins by NO Donors in Rat Embryonic Fibroblast 3Y1 Cells: Factors Affecting S-Nitrosation. (17th August 2011) - Ryuman, Norihiro; Watanabe, Nobuo; Arai, Takao
Abstract : The mechanism of protein S-nitrosation in cells is not fully understood. Using rat 3Y1 cells, we addressed this issue. Among S-nitrosothiols and NO donors tested, only S-nitrosocysteine (CysNO) induced S-nitrosation when exposed in Hanks' balanced salt solution (HBSS) and not in serum-containing general culture medium. In HBSS, NO release from CysNO was almost completely abolished by sequestering metal ions with a metal chelator without affecting cellular S-nitrosation. In contrast, L-leucine, a substrate of L-type amino acid transporters (LATs), significantly inhibited S-nitrosation. The absence of S-nitrosation with CysNO in general culture medium resulted not only from a competition with amino acids in the medium for LATs but also from transnitrosation of cysteine residues in serum albumin. Collectively, these results suggest that in simple buffered saline, CysNO-dependent S-nitrosation occurs through a cellular incorporation-dependent mechanism, but if it occurs in general culture media, it may be through an NO-dependent mechanism.